The Effect of Youth Education on Student Discipline in State Vocational High School 5 Tangerang Regency - Isti Mukhairiyah; Ratna Sari Dewi; Wika Hardika Legiani (CV. Rayyan Dwi Bharata, 2022)
This research was conducted with the aim of determining the influence of youth education on student discipline at State Vocational High School 5 Tangerang Regency, the application of youth education in schools, as well as violations after students have attended youth education carried out at State Vocational High School 5 Tangerang Regency, with the existence of youth education is expected to provide benefits to the development of science in the education section, especially regarding the enforcement of learner discipline. The type of research conducted by the author is quantitative research research, the population in this study is students of State Vocational High School 5 Tangerang Regency while the sampling technique uses the Slovin formula. In this study, researchers will take random samples with experimental classes that have implemented youth education, namely eleventh grade (XI) and twelfth grade (XII) while tenth grade (X) is a control class because they have not attended youth education. The data retrieval technique uses a questionnaire with a 5-point Likert scale and the data is processed and analyzed with statistical techniques using the SPSS version 26 program application. After the test results obtained a Sig. value of 0.000 0.05 and a calculated t value of 142.294 t table 0.67700, it can be decided that there is an influence of independent variables on the dependent. The magnitude of the influence of the experiment variable 0.952 x 100 = 95.2 % is influenced by the variable X, and the comparison variable or control class calculation 0.562 x 100 = 56.2%. This proves that there is a significant influence between youth education on student discipline at State Vocational High School 5 Tanagerang Regency.